The Micro and Macro Effects of Changes in the Potential Benefit Duration - Jonas Jessen; Robin Jessen; Ewa Galecka-Burdziak; Marek Góra; Jochen Kluve (Institute of Labor Economics (IZA), 2023)
We quantify micro and macro effects of changes in the potential benefit duration (PBD) in unemployment insurance. In Poland, the PBD is 12 months for newly unemployed if the previous year's county unemployment rate is more than 150% of the national average, and 6 months otherwise. We exploit this discontinuity using RD estimates on registry data containing the universe of unemployed from 2004 to 2020. For workers whose PBD is directly affected by the policy rule (benefit recipients younger than 50), a PBD increase from 6 to 12 months leads to 13 percent higher unemployment. The aggregate effect on unemployment is entirely explained by this increase. Thus, the micro effect equals the macro effect. We find no evidence of spill-overs on two distinct groups of unemployed whose PBD is unchanged and no effect on measures of labour market tightness. A decomposition analysis reveals that 12 months after an increase in the PBD, changes in exits from and entries into unemployment each contribute to about one half of the overall increase in unemployment.
Keywords: H55; J20; J65; 330; unemployment benefits; extended benefits; spell duration; separation rate; regression discontinuity